Analisis kesalahan mahasiswa PGMI dalam menyelesaikan soal cerita bilangan bulat dan pecahan berdasarkan teori Kastolan - Maryanti, Era; Rahmat, Rahmat; Erwin, Erwin (Diniyah: Jurnal Pendidikan Dasar, 2025)
Mathematical word problem-solving is a crucial competence for Primary Madrasah Teacher Education students as prospective elementary teachers. This study aimed to analyze the errors made by PGMI students in solving word problems involving integers and fractions based on Kastolan’s error analysis theory. A descriptive qualitative approach supported by simple quantitative analysis was employed. The participants were 48 second-semester PGMI students at IAIN Kendari who had completed an elementary mathematics course. Data were collected through written tests, semi-structured interviews, and documentation, then analyzed by classifying errors into conceptual, procedural, and technical categories. The findings revealed 288 error units, consisting of procedural errors as the most dominant category with 120 occurrences or 41.67%, followed by conceptual errors with 101 occurrences or 35.07%, and technical errors with 67 occurrences or 23.26%. The results indicate that students’ difficulties were mainly related to organizing systematic solution procedures and understanding mathematical concepts in contextual situations. These findings imply the need for more diagnostic, conceptual, and reflective mathematics instruction in PGMI programs. Keywords: error analysis; fractions; integers; Kastolan’s theory; mathematical word problems; PGMI students; prospective elementary teachers